2016
DOI: 10.1007/s10570-016-0991-1
|View full text |Cite
|
Sign up to set email alerts
|

On the anomalous temperature dependence of cellulose aqueous solubility

Abstract: The solubility of cellulose in water-based media is promoted by low temperature, which may appear counter-intuitive. An explanation to this phenomenon has been proposed that is based on a temperature-dependent orientation of the hydroxymethyl group. In this paper, this hypothesis is investigated using molecular dynamics computer simulations and NMR spectroscopy, and is discussed in conjunction with alternative explanations based on solvent-solute and solvent-solvent hydrogen bond formation respectively. It is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…In addition to this, the 3 J HH couplings remained unchanged within our temperature window, which is in accord with the results found by others (Bergenstråhle-Wohlert et al 2016). This indicates that the conformational change of the hydroxymethyl group is not induced by a temperature change within the dissolution temperature window.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition to this, the 3 J HH couplings remained unchanged within our temperature window, which is in accord with the results found by others (Bergenstråhle-Wohlert et al 2016). This indicates that the conformational change of the hydroxymethyl group is not induced by a temperature change within the dissolution temperature window.…”
Section: Resultssupporting
confidence: 93%
“…Concerning the influence of urea on the hydrophobic interactions in cellulose, Bergenstråhle-Wohlert et al (2012) and Wernersson et al (2015) reported on the accumulation of urea close to the hydrophobic surfaces on cellulose in water without alkali using MD simulations while Xiong et al (2014) and Isobe et al (2012) suggested from experimental results that an accumulation of urea in the cellulose/NaOH or LiOHsystem on the hydrophobic part of the cellulose occurred to prevent agglomeration of the chains. In the work by Cai et al (2008), experimental results indicated that NaOH hydrates were in favour to bind to cellulose chains through the formation of a new hydrogen-bonded network at low temperatures in contrast to urea hydrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the equal change for H5 could not be observed due to overlap with H3. Interestingly, the same proton is affected upon dissolution of the b-MeO-Glcp in NaOH(aq) (the only 3 J HH changes observed when going from NaCl(aq) to NaOH(aq) solvent) due to the well-known conformation change of the primary hydroxyl from tg to gt in aqueous solutions (Horii et al 1983;Bergenstråhle-Wohlert et al 2016). Addition of CO 2 (g) prior to carbohydrate did not affect the 3 J HH couplings.…”
Section: Resultsmentioning
confidence: 90%